Transcranial 1064-nm laser photobiomodulation modulates frequency-specific cortical source dynamics and functional connectivity in healthy adults - Bastola, Subrat; Pruitt, Tyrell; Davenport, Elizabeth M.; Maldjian, Joseph A.; Liu, Hanli; Alexandrakis, George (Frontiers in Human Neuroscience, 2026)
IntroductionTranscranial photobiomodulation (tPBM) with near-infrared light is a promising non-invasive method to enhance cognition and support brain health. However, its mechanistic effects on large-scale cortical dynamics remain poorly understood. Establishing how tPBM reorganizes oscillatory hierarchies is critical for advancing both neuroscience and clinical translation.MethodsWe examined whether acute 1,064-nm tPBM modulates oscillatory power, dipole source trajectories, and functional connectivity in the human brain. Simultaneous magnetoencephalography (MEG) and electroencephalography (EEG) were recorded in 25 healthy adults before and after prefrontal tPBM. Distributed source imaging (sLORETA) and global optimization dipole modeling characterized spatiotemporal alpha and beta activity. Connectivity was assessed with phase transfer entropy, and infra-slow phase–amplitude coupling analyses assessed hierarchical modulation.ResultsTranscranial photobiomodulation induced frequency-specific reorganization of cortical networks. Alpha oscillations engaged coordinated fronto–visual circuits, whereas beta activity preferentially recruited higher-order executive regions. Source imaging revealed a post-stimulation shift from default mode toward central executive network dominance with stronger directed interactions. Infra-slow rhythms (<0.1 Hz), encompassing both very-low-frequency (0.01–0.1 Hz) and ultra-slow (<0.01 Hz) activity, significantly modulated alpha- and beta-band amplitudes, embedding faster oscillations within slower temporal patterns.DiscussionThe findings of his work indicate that tPBM influences intrinsic brain activity by reorganizing oscillatory patterns and shifting network engagement. The redistribution from default mode toward executive systems, along with the nesting of faster rhythms within slower temporal structures, reflects a capacity for large-scale functional rebalancing. The results highlight tPBM’s potential as a precision neuromodulation tool for modulating executive and cognitive control systems.